Loyalty to Community Modeling Through Value Co-Creation Behavior Activities With Perceived Benefit Mediation: Organic Food Product - Maya Maria; Ujang Sumarwan; Ahmad Sulaeman; Agus W. Soehadi (Jurnal Manajemen & Agribisnis, 2021)
The current trend of people's lifestyles is to start consuming foods that are safe and environmentally friendly. The development of information on the usefulness of organic products more broadly becomes necessary. This study aims to determine the impact of value co-creation activities on loyalty to community, mediated by perceived benefit value. The analysis tool used in this study is Structural Equation Model (SEM) analysis. The sampling method used is a convenience sampling approach with 385 respondents. The results show that consumer perceived benefits value have a strong effect on loyalty to the community. In addition, value co-creation activities in the community is shown to be measurable by customer participation behavior and customer citizenship behavior to obtain the desired perceived benefits. The role of the community with the support of the loyalty of its members can be an effective means of disseminating knowledge about organic food products more broadly to the public. Having these results, the recommended policy direction is to increase the perceived benefits of customer community participation and citizenship. Further studies are needed to refine and build a more comprehensive model that integrates other theoretically related constructs. Keywords: customer participation behavior, customer citizenship behavior, loyalty to community, organic food products, perceived benefit